Miscarriage, SUDI and neonatal death: paramedic experience and practice. (2nd December 2020) - Reed, Kate; Ferazzoli, Maria Teresa; Whitby, Elspeth
Abstract : This article aims to provide an exploratory investigation into paramedic experiences of attending cases of miscarriage, sudden and unexpected death in infancy (SUDI) and other forms of neonatal loss. It draws on a background literature review, but focuses primarily on exploring issues raised by paramedics during a structured discussion group on this topic. Existing literature highlights the ways in which baby and infant death is one of the most stressful and challenging areas of paramedic practice. Paramedics participating in our discussion group reinforced this issue, identifying five key areas of concern: baby loss as a rare occurrence, resuscitation, lack of information concerning the post-admissions process, professional closure, and support to parents. Further research is needed, along with better support and guidelines to assist paramedics with a wide range of issues from resuscitation to bereavement.